First, rewrite the expression using this rule for exponents:
#a = a^color(red)(1)#
#12/4(a^-2/a^-8)(b^-4/b^color(red)(1)) =>#
#3(a^-2/a^-8)(b^-4/b^color(red)(1))#
Next, use this rule of exponents to simplify the #a# terms:
#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#
#3(a^color(red)(-2)/a^color(blue)(-8))(b^-4/b^1) =>#
#3a^(color(red)(-2)-color(blue)(-8))(b^-4/b^1) =>#
#3a^(color(red)(-2)+color(blue)(8))(b^-4/b^1) =>#
#3a^6(b^-4/b^1)#
Now, use this rule of exponents to simplify the #b# term:
#x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))#
#3a^6(b^color(red)(-4)/b^color(blue)(1)) =>#
#3a^6(1/b^(color(blue)(1)-color(red)(-4))) =>#
#3a^6(1/b^(color(blue)(1)+color(red)(4))) =>#
#3a^6(1/b^5) =>#
#(3a^6)/b^5#